ANALISIS PERFORMA HEAT EXCHANGER OIL COOLER UPPER TIPE M10-BFG PADA UNIT 1,2,3,4 PLTA SINGKARAK UNTUK TINDAKAN PEMELIHARAAN - Didik Agung Nugroho; Mukhnizar; Risal Abu; Afdal; Azmil Azman (Journal of Scientech Research and Development, 2023)
ABSTRACT Heat Exchanger is equipment used to carry out the process of exchanging heat between two fluids, either liquid (hot or cold) or gas, where these fluids have different temperatures. Singkarak hydropower plant also uses a plate type heat exchanger with the code M10-BFG in operation. Serves to exchange heat in the oil used in the upper oil pot, which functions as a cooler and lubricant for the upper bearing and thrust bearing. Seeing the function of the upper and thrust bearings, which are two important bearings in the unit. A good maintenance process is needed on the plate heat exchanger to maintain the condition of the oil at working temperature, which is at 45-55 0C. Through this research, the authors analyzed the performance of the M10-BFG plate heat exchanger with the parameters of the actual heat transfer coefficient and monthly temperature trends. After doing research with quantitative methods through data collection and data processing, it was found that unit 4 has the highest actual heat transfer coefficient of 875.666-900.574 W, but has the shortest usage time, for 42 days based on the existing trending temperature. This is because in unit 4 the oil flow (870-900 l/minute) is below standard, and the size of the heat exchanger plate (55 cm) has shrunk far from the initial value (63 cm). So it is necessary to carry out corrective maintenance on unit 4. Meanwhile, the lowest actual heat transfer coefficient is found in unit 1 with a value of 706.797-770.027 W and the longest plate heat exchanger usage time is in unit 3, with an estimated 121 days before reaching the 55 0C alarm.